The importance of practical rationality in the conjuncture of the COVID-19 pandemic - García-Sauñe, Julio D. (2020)
In a situation such as the spread of the covid-19 virus, it is inevitable to ask questions that challenge everything that is established. Any order is questioned, albeit at different levels and intensity, whether in the political, social, economic, ethical or ontological field. As children of modernity we still have full confidence in the clear separation between these "spheres" and when, rather, part of this whole crisis has to do with such an assumption. On this occasion, briefly, we are going to focus on the implicit questions of the ethical order in the context of the pandemic in order to show the relevance of Aristotelian ethics, albeit with some nuances, for a better resolution of some moral conflicts that have arisen. In this sense, this work will be divided into three parts: firstly, we will present the central ideas of Aristotelian ethics; secondly, we will show their relevance for the resolution of some ethical dilemmas generated by the pandemic and, thirdly, we will highlight the relevance of practical rationality today.